Differences in the Effectiveness of Papaya and Guava on Hemoglobin Levels of Pregnant Women at the Nagaswidak Health Center - Tri Restu Handayani; Devina Anggrainy Dencik (Journal of Educational Innovation and Public Health, 2024)
World Health Organization (WHO) 41% of pregnant women worldwide experience anemia. Overall, the prevalence of anemia in pregnant women in developed countries is 49% and in developing countries it is 53%. In Indonesia, the rate of anemia in pregnant women is quite high, namely 48.9%. Anemia that is commonly experienced by pregnant women is iron deficiency anemia. Iron is needed in hemopoesis (blood formation), namely in the synthesis of hemoglobin. Iron absorption can be increased by consuming ± 25 mg of vitamin C sources in food. The aim of the research was to determine the difference in the effectiveness of papaya and red guava on hemoglobin levels in pregnant women with anemia. The research was conducted at the Nagaswidak Community Health Center in June 2024 using a quasi-experimental two group pretest and posttest. The population in this study were all pregnant women who were in the working area of the Nagaswidak Palembang Community Health Center in May 2024 with Hb levels of 9 – 10.9 gr/dl. The sampling technique used purposive sampling totaling 30 respondents. The results of the Wilcoxon test research showed that the effect of papaya (p value 0.000) and guava (p value 0.000) was obtained. The results of the Mann Whitney union obtained a p value of 0.116. There is an effect of papaya on hemoglobin levels in pregnant women, there is an effect of guava on hemoglobin levels. There is no difference in the effect of papaya and guava on hemoglobin levels in pregnant women at the Nagaswidak Community Health Center. It is hoped that health workers will increase education regarding the prevention of anemia in pregnant women, one of which is by consuming vitamin C in fruit.